The Prognostic Impact of Pretreatment Geriatric Nutritional Risk Index in Patients with Diffuse Large B-Cell Lymphoma. (7th February 2023) - Atas, Unal; Sozel, Hasan; Iltar, Utku; Yucel, Orhan Kemal; Salim, Ozan; Undar, Levent
Abstract: The prognostic value of the geriatric nutritional risk index (GNRI) is not clear in patients with diffuse large B-cell lymphoma (DLBCL). This study was designed to analyze the GNRI in DLBCL patients and to investigate its prognostic value in DLBCL. The archive records of DLBCL patients between 2008 and 2020 at the Akdeniz University Hospital were retrospectively analyzed. A total of 206 patients with DLBCL were recruited and classified into two GNRI-based groups based on nutrition status. The GNRI cut off value was determined by ROC analysis. In the univariate Cox regression analysis for overall survival (OS), age, lactate dehydrogenase, B symptoms, infiltration of bone marrow, and the GNRI were determined as prognostic factors for mortality. The OS of patients with a GNRI ≤104.238 was significantly lower than that of patients with a GNRI >104.238 ( p = 0.001). The progression-free survival (PFS) of patients with GNRI ≤104.238 was significantly lower compared to the patients with GNRI >104.238 ( p = 0.010). Based on the results of the present study with a relatively large hospital-based cohort, the GNRI can be recommended for use as an independent prognostic marker for OS and PFS in patients with DLBCL.